2008
DOI: 10.1177/1043659608317095
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Support Recruitment and Retention of First Nations Youth in Baccalaureate Nursing Programs in Saskatchewan, Canada

Abstract: Aboriginal youth is one of the fastest growing of all populations in Saskatchewan today. This is a prime group to target for training in the health care professions. The need for strategies to support recruitment and retention in these programs is critical for maintaining our present standard and increasing demands of quality health care. Program initiatives and supports need to be implemented to encourage this population to enroll in and complete health care programs. Although only 5 years old, the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 15 publications
(15 reference statements)
3
35
0
Order By: Relevance
“…Aboriginal student experiences highlight factors specific to living conditions, fears and anxieties, inadequate educational preparation, culture shock when relocating to urban areas, a lack of Indigenous mentors and financial hardship (Anonson, Desjarlais, Nixon, Whiteman, & Bird, 2008;Martin & Kipling, 2006;Usher, Lindsay, Miller, & Miller, 2005). Aboriginal student experiences highlight factors specific to living conditions, fears and anxieties, inadequate educational preparation, culture shock when relocating to urban areas, a lack of Indigenous mentors and financial hardship (Anonson, Desjarlais, Nixon, Whiteman, & Bird, 2008;Martin & Kipling, 2006;Usher, Lindsay, Miller, & Miller, 2005).…”
Section: Aboriginal Student Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aboriginal student experiences highlight factors specific to living conditions, fears and anxieties, inadequate educational preparation, culture shock when relocating to urban areas, a lack of Indigenous mentors and financial hardship (Anonson, Desjarlais, Nixon, Whiteman, & Bird, 2008;Martin & Kipling, 2006;Usher, Lindsay, Miller, & Miller, 2005). Aboriginal student experiences highlight factors specific to living conditions, fears and anxieties, inadequate educational preparation, culture shock when relocating to urban areas, a lack of Indigenous mentors and financial hardship (Anonson, Desjarlais, Nixon, Whiteman, & Bird, 2008;Martin & Kipling, 2006;Usher, Lindsay, Miller, & Miller, 2005).…”
Section: Aboriginal Student Characteristicsmentioning
confidence: 99%
“…Similarly, Yurkovich (2001) argued that Aboriginal students who enter Euro-Anglo educational settings become "painfully aware that their values, beliefs, and practices are in conflict with many practices and procedures of the educational culture" (p. 268). The presence of culturally relevant social supports, such as Indigenous mentorship and role models in educational institutions (Anonson et al, 2008;Martin & Kipling, 2006;Turale & Miller, 2006;Usher, Cook et al, 2005;Usher, Lindsay, Miller et al, 2005), and appropriate tutoring (Anonson et al, 2008;Hobenshield, Scow & Drees, 2007) were found to positively influence Aboriginal nursing students' social experiences in university or college. This lack is perceived by Aboriginal students to be a considerable barrier to their academic success (Usher, Lindsay, Miller et al, 2005).…”
Section: Transition To Universitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the fi eld of nur ing, the Uni' cr~tt y of Saskatchewan credits thei r ht gher retention of Indi genous students and gradu ates to the creation of formal n1e ntor~h1p and professional de\ elopn1ent progratns They ~pecdica ll y recruited and tratncd Ind1 genou~ students to take on the e roles creating ~p ace for n1ore Indi genous educators'" 1th1n the health ca re fi eld (Anonson, et aL 2008). They have partnered with other con1n1untty par1ncrs and disciplines to recruit Indi genou s n1 cntors to support an Indigenou s perspecti ve withtn learning.…”
mentioning
confidence: 99%